Mechanistic analyses of the suppression of amyloid β42 aggregation by apomorphine. Issue 8 (1st May 2018) - Hanaki, Mizuho; Murakami, Kazuma; Katayama, Sumie; Akagi, Ken-ichi; Irie, Kazuhiro
Graphical abstract: Abstract: ( R )-Apomorphine (1 ) has the potential to reduce the accumulation of amyloid β-protein (Aβ42), a causative agent of Alzheimer's disease (AD). Although the inhibition of Aβ42 aggregation by 1 is ascribable to the antioxidative effect of its phenol moiety, its inhibitory mechanism at the molecular level remains to be fully elucidated. LC–MS and UV analyses revealed that 1 is autoxidized during incubation to produce an unstable o -quinone form (2 ), which formed a Michael adduct with Lys 16 and 28 of Aβ42. A further autoxidized form of 1 (3 ) with o -quinone and phenanthrene moieties suppressed Aβ42 aggregation comparable to 1, whereas treating 1 with a reductant, tris(2-carboxyethyl)phosphine diminished its inhibitory activity. 1 H- 15 N SOFAST-HMQC NMR studies suggested that 1 interacts with Arg5, His13, 14, Gln15, and Lys16 of the Aβ42 monomer. These regions form intermolecular β-sheets in Aβ42 aggregates. Since 3 did not perturb the chemical shift of monomeric Aβ42, we performed aggregation experiments using 1, 1, 1, 3, 3, 3-hexafluoro-2-propanol-treated Aβ42 to investigate whether 3 associates with Aβ42 oligomers. Compounds 1 and 3 delayed the onset of the oligomer-driven nucleation phase. Despite their cytotoxicity, they did not exacerbate Aβ42-mediated neurotoxicity in SH-SY5Y neuroblastoma cells. These results demonstrate that extension of the conjugated system in 1 by autoxidation can promote its planarity, which is required for intercalation into the β-sheet of Aβ42 nuclei, thereby suppressing further aggregation.